The Effectiveness of the Inclusive Education Model for Students With Special Needs on Cognitive Learning Achievement - Herpratiwi, Herpratiwi (Jurnal Pendidikan Progresif, 2018)
The effectiveness of the inclusive education model for students with special needs on cognitive learning achievement. Objectives: This research aims to analyze the influence of the inclusive education model in the form ofthe regular class with additional instruction outside the classroom on cognitive learning achievement of elementary school students in Lampung Province. Methods: Samples consist of 35 fifth grade elementary school students which were randomly selected from a population of 245 out of seven schools in seven regencies in Lampung Province, Indonesia. Data were analyzed using the paired samples t-test at the significance level of 0.05 for all subjects. This research applied a quasi-experimental design. Findings: Value of t-count (6.249) for General Knowledge was greater than t-table at the significance level 0.05 which confim the effectivity of the model. Conclusions:Inclusive education model had an effective influence on the learning achievement of students with special needs in the General Knowledge subject.Keywords: Children with special needs, cognitive learning achievement, inclusive education model DOI: http://dx.doi.org/10.23960/jpp.v8.i2.201811